Analysis of risk factors for late postoperative pleural effusion in patients undergoing single-port thoracoscopic lung surgery - WANG Qin; XIA Guanghui; JIANG Jie; YANG Xiaoxin; DING Jiefang; YIN Ying; WU Guanghong; LIU Feng; CAO Hui; SHI Ye (Zhongguo linchuang yanjiu)
Objective To explore the risk factors of late postoperative pleural effusion in patients undergoing single-port thoracoscopic lung surgery, and to provide a basis for the whole-process management of surgical patients. Methods A retrospective analysis was conducted on the clinical data of 140 patients who underwent single port thoracoscopic lung surgery at the Department of Thoracic Surgery of Nanjing Chest Hospital from December 2021 to October 2022. According to the amount of pleural effusion, they were divided into four groups: no pleural effusion group (n=42), mild pleural effusion group (n=58), moderate pleural effusion group (n=11), and severe pleural effusion group (n=29). Univariate analysis and ordinal logistic regression analysis were used to compare the following variables: gender, age, body mass index, smoking history, complications, or previous history (hypertension, diabetes, coronary heart disease, tuberculosis), pleural thickening, chest adhesion, surgical technique and lymph node dissection, postoperative active breathing training, dietary habits (high protein diet, high fat diet, and average daily soup consumption). Results Univariate analysis showed that lobectomy (χ2=8.469, P=0.037), lymph node dissection (χ2=13.027, P=0.005), postoperative high protein diet (χ2=13.719, P=0.003), postoperative high fat diet (χ2=49.374, P＜0.001), and daily soup consumption (Z=30.707, P＜0.001) were associated with the amount of late postoperative pleural effusion in pulmonary surgery patients. The results of ordinal logistic regression analysis showed that high fat diet (OR=7.114, 95%CI: 3.191-15.877) and high mean daily soup consumption (OR=1.167, 95%CI: 1.062-1.283) were risk factors for late pleural effusion in patients undergoing lung surgery, while high protein diet (OR=0.229, 95%CI: 0.077-0.676) was a protective factor. Conclusion The amount of delayed pleural effusion after lung surgery is related to the early postoperative diet. Patients with a high fat diet and high daily soup consumption have a high risk of delayed pleural effusion, while high protein diet can reduce the risk of delayed pleural effusion.